REKONSTRUKSI PENDIDIKAN ISLAM DALAM PERUBAHAN MINDSET MASYARAKAT GUNUNG KEMUKUS - Hidayat, Aat (EDUKASIA, 2018)
Gunung Kemukus is one of the most sacred regions in Sragen, Central Java. In that area, there is tomb of Pangeran Samudera who is known as an Islamic disseminator of Majapahit descent who received religious guidance from Sunan Kalijaga. However, the spiritual sacredness is damaged by the practice of rituals of self enrichment with committing seven times of sexual adultery rituals on Jumat Pon. Ironically, this practice was responded to fairly by the community that knows the religion values well. This condition is caused by the mindset formed so that the grave pilgrimage ritual followed by the practice of prostitution is a legitimate activity and does not conflict with social and religious norms. This research examined more about how the reconstruction of Islamic education held in the region so that the later generation has begun to change their mindset in response to the rituals on Gunung Kemukus. It is expected that this Islamic education model will support the policy of Sragen Regency government that tries to control the tourist sites of Gunung Kemukus which are often used as prostitution locations covered by grave pilgrimages and self enrichment rituals.